Gender and intersecting vulnerabilities on the mental health unit: Rethinking the dilemma - Morton, Elizabeth Kathleen; McKenzie, Sarah K.; Cooper, Amy; Every-Palmer, Susanna; Jenkin, Gabrielle Lisa Simone (Frontiers in Psychiatry, 2022)
Abstract Background: Gender is routinely pitched as a key determinant of vulnerability for staff and residents on acute mental health inpatient units. Since the 1960s mixed gender units have become more prominent in Western health systems, yet questions remain around the configuration of these units, including how to ensure emotional and physical safety of those living and working in them. Methods: This paper draws on a large study of the lived experiences of 42 staff and 43 service users from different acute mental health units in New Zealand. We conducted thematic analysis of interview data from four units with diverse architectural layouts to identify key themes central to decisions around gender and spatial design. Results: Key themes emerged around gender-related trauma histories, safety perceptions and vulnerabilities, accommodation of gender-diverse and non-binary mental health service users, and gender-specific needs and differences. A further theme, of it goes beyond gender emphasised that there are many other non-gender attributes that influence vulnerability on the unit. Conclusions: While findings emphasise the need for safe places for vulnerable people, trauma-informed care, access to staff who ‘understand’, and recreation that is meaningful to the individual, we question if the dilemma of gender-separation versus gender-mixing is an outmoded design consideration. Instead, we argue that a flexible, person-centred approach to provision of care, which values autonomy, privacy, and safety as defined by each service user, and that promotes choice-making, obviates a model where gender accommodations are fore. We found that a gender-exclusive narrative of vulnerability understates the role of other identifiers in dynamics of risk and vulnerability, including age, physicality, past violence, trauma history, mental unwellness, and substance use. We conclude gender need not be a central factor in decisions around design of prospective built unit environments or in occupational and clinical decisions. Instead, we suggest flexible spatial layouts that accommodate multiple vulnerabilities.